Short term sodium alendronate administration improves the per. implant bone quality in osteoporotic animals - Oliveira, Danila de [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Silva Gomes-Ferreira, Pedro Henrique da [UNESP]; Braga Polo, Tarik Ocon [UNESP]; Ferreira, Gabriel Ramalho; Faverani, Leonardo Perez [UNESP]; Okamoto, Roberta [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2017)
Sodium alendronate is a bisphosphonate drug that exerts antiresorptive action and is used to treat osteoporosis. Objective: The aim of this study was to evaluate the bone repair process at the bone/implant interface of osteoporotic rats treated with sodium alendronate through the analysis of microtomography, real time polymerase chain reactions and immunohistochemistry (RUNX2 protein, bone sialoprotein (BSP), alkaline phosphatase, osteopontin and osteocalcin). Material and Methods: A total of 42 rats were used and divided in to the following experimental groups: CTL: control group (rats submitted to fictitious surgery and fed with a balanced diet), OST: osteoporosis group (rats submitted to a bilateral ovariectomy and fed with a low calcium diet) and ALE: alendronate group (rats submitted to a bilateral ovariectomy, fed with a low calcium diet and treated with sodium alendronate). A surface treated implant was installed in both tibial metaphyses of each rat. Euthanasia of the animals was conducted at 14 (immunhostochemistry) and 42 days (immunohistochemistry, micro CT and PCR). Data were subjected to statistical analysis with a 5% significance level. Results: Bone volume (BV) and total pore volume were higher for ALE group (P<0.05). Molecular data for RUNX2 and BSP proteins were significantly expressed in the ALE group (P<0.05), in comparison with the other groups. ALP expression was higher in the CTL group (P<0.05). The immunostaining for RUNX2 and osteopontin was positive in the osteoblastic lineage cells of neoformed bone for the CTL and ALE groups in both periods (14 and 42 days). Alkaline phosphatase presented a lower staining area in the OST group compared to the CTL in both periods and the ALE at 42 days. Conclusion: There was a decrease of osteocalcin precipitation at 42 days for the ALE and OST groups. Therefore, treatment with short-term sodium alendronate improved bone repair around the implants installed in the tibia of osteoporotic rats.
Keywords: Alendronate; Osseointegration; Osteoporosis